Comparative breeding ecology of Mississippi Kites in urban and exurban areas of West Texas. Issue 3 (14th August 2019) - Welch‐Acosta, Brandi C.; Skipper, Ben R.; Boal, Clint W.
Abstract: Birds of prey are becoming increasingly common occupants of urbanized settings, but the comparative benefits or detriments they experience in urban environs compared to exurban areas are poorly understood. We examined the reproductive success and phenology of Mississippi Kites ( Ictinia mississippiensis ) nesting concurrently in urban and exurban areas in west Texas during the 2010–2012 and 2014 breeding seasons. Our objective was to better understand the reproductive advantages or disadvantages that kites may experience by nesting in urban areas rather than exurban areas. We calculated annual productivity, estimated daily survival rates of nests, and estimated hatch dates. Kites produced 0.52 fledglings per urban nesting attempt and 0.33 fledglings per exurban nesting attempt. We found no difference in the mean number of young that fledged from successful urban (1.06) and exurban (1.07) nests, but kites in urban areas had greater nesting success within years than those in exurban areas. Both heat and drought were associated with low productivity and success in both areas, but the urban landscape appears to have provided some buffer to their effects. These factors may have had direct (e.g., exposure) or indirect (e.g., negative influences on prey availability) influences on reproductive success. Counter to previous studies of urban raptors, we found that exurban kites nested significantly earlier than urban kites. This may be linked to differences in environmental conditions and prey availability between the areas. Our results suggest that urban areas provide a reproductive advantage for Mississippi Kites in terms of facilitating an overall higher nesting success, but this does not translate into increased productivity for successful pairs. Further, our data suggest that, although urban areas may buffer species from drought or heat, that buffer can be breached during severe conditions. Resumen: Ecología reproductiva comparativa del Milano de Mississippi en áreas urbanas y periurbanas del oeste de Texas Las aves de presa se están convirtiendo en ocupantes cada vez más comunes de zonas urbanas, pero los beneficios o perjuicios comparativos que experimentan en ambientes urbanos comparados a ambientes periurbanos están pobremente entendidos. Examinamos el éxito reproductivo y la fenología de los Milanos de Mississippi ( Ictinia mississippiensis ) anidando al mismo tiempo en áreas urbanas y periurbanas en el oeste de Texas durante las temporadas reproductivas del 2010 al 2012. Nuestro objetivo fue comprender mayor las ventajas o desventajas reproductivas que los milanos pueden experimentar al anidar en áreas urbanas en vez de periurbanas. Calculamos la productividad anual, la tasa diaria estimada de supervivencia de nido, y las fechas estimadas de eclosión. Los milanos producen 0.52 volantones por intento de nido en zona urbana y 0.33 volantones por intento de nido en zonas periurbanas. Aún así, no encontramos diferencias en el número medio de juveniles que se desarrollan en nidos exitosos urbanos (1.06) y periurbanas (1.07), pero los milanos en áreas urbanas tienen mayor éxito de nidada dentro de estos años que los nidos en zonas periurbanas. Tanto el calor como la sequía fueron asociadas con la baja productividad y éxito en ambas áreas, pero el paisaje urbano parece proveer alguna amortiguación a sus efectos. Estos factores pueden tener una influencia directa (e. g., exposición) o indirecta (e. g., influencia negativa en la disponibilidad de presas) en el éxito reproductivo. A diferencia de estudios previos en rapaces urbanas, encontramos que los milanos periurbanas anidan significativamente más temprano que los milanos periurbanas. Esto puede estar relacionado a diferencias en las condiciones ambientales y en la disponibilidad de presas entre las áreas. Nuestros resultados sugieren que las áreas urbanas proveen una ventaja reproductiva al Milano de Mississippi en términos de facilitar un éxito de nidada en general mayor, pero esto no se traduce a una mayor productividad en parejas exitosas. Aún más, nuestros datos sugieren que, a pesar de que las áreas urbanas pueden proteger a las especies de la sequía o el calor, esa protección puede ser ineficiente durante condiciones severas.